Involvement of chondroitin sulfate synthase-3 (chondroitin synthase-2) in chondroitin polymerization through its interaction with chondroitin synthase-1 or chondroitin-polymerizing factor - Izumikawa, Tomomi (Portland Press Ltd., 2007)
Previously, we have demonstrated that co-expression of ChSy-1 (chondroitin synthase-1), with ChPF (chondroitin-polymerizing factor) resulted in a marked augmentation of glycosyltransferase activities and the expression of the chondroitin polymerase activity of ChSy-1. These results prompted us to evaluate the effects of co-expression of the recently cloned CSS3 (chondroitin sulfate synthase-3) with ChPF, because ChSy-1 and CSS3 have similar properties, i.e. they possess GalNAcT-II (N-acetylgalactosaminyltransferase-II) and GlcAT-II (glucuronyltransferase-II) activities responsible for the elongation of CS (chondroitin sulfate) chains but cannot polymerize chondroitin chains by themselves. Co-expressed CSS3 and ChPF showed not only substantial GalNAcT-II and GlcAT-II activities but also chondroitin polymerase activity. Interestingly, co-expressed ChSy-1 and CSS3 also exhibited polymerase activity. The chain length of chondroitin formed by the co-expressed proteins in various combinations was different. In addition, interactions between any two of ChSy-1, CSS3 and ChPF were demonstrated by pull-down assays. Moreover, overexpression of CSS3 increased the amount of CS in HeLa cells, while the RNA interference of CSS3 resulted in a reduction in the amount of CS in the cells. Altogether these results suggest that chondroitin polymerization is achieved by multiple combinations of ChSy-1, CSS3 and ChPF. Based on these characteristics, we have renamed CSS3 ChSy-2 (chondroitin synthase-2).